Empowering the Community of Kubangsari Village, Cilegon City, through Innovation in Processing Corn into Corn Syrup as an Effort to Increase Local Economic Income - Sholihin, Miftahus; Sari, Putri Dina; Abdullah, Syarif; Wicaksono, Agung Satrio; Erda, Gustriza; Rivai, Muklas; Anwaar Al'Fathoni, Muhammad Khoirul; Lidyasari, Nadia Bintang (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
The majority of the community in Kubangsari Village, Cilegon City, are farmers and factory workers, with approximately 20% of the population directly dependent on the corn farming sector. Traditionally, corn harvests have been sold raw at prices around IDR 8,000, leaving farmers vulnerable to economic fluctuations, particularly during the rainy season when fields are prone to flooding. This community service program aims to empower the Kubang Lestari Women Farmers Group (KWT) through the innovation of processing purple corn into a functional health beverage named JAJANTAN (Jahe Jagung Anti Oksidan/Ginger Corn Antioxidant). The implementation method spanned one month, involving field surveys, direct production workshops, and assistance in packaging and halal certification. The results demonstrated a significant increase in the added value of agricultural commodities; raw corn was transformed into a ready-to-sell bottled beverage priced at IDR 10,000 per unit, with a production cost of IDR 7,000. This mentorship has successfully increased public knowledge regarding food product diversification and opened opportunities for the development of local Micro, Small, and Medium Enterprises (MSMEs), with full support from the local village government.